A cobalt tungstate compound sensing electrode for hydrogen detection based upon mixed-potential type sensors. Issue 5 (12th January 2017) - Li, Y.; Li, X.; Wang, J.; Jun, Y.; Tang, Z.
Abstract : An yttria-stabilized cubic zirconia (YSZ) based mixed-potential sensor coupled with CoWO4 as the sensing electrode was developed for hydrogen detection at elevated temperatures. Abstract : An yttria-stabilized cubic zirconia (YSZ) based mixed-potential sensor coupled with CoWO4 as the sensing electrode was developed for hydrogen detection at elevated temperatures. The developed CoWO4 /YSZ/Pt sensor was found to have a good sensitivity to different concentrations of hydrogen from 80 ppm to 960 ppm in a background of 10% O2 /N2 at 450 °C. The sensor showed excellent selectivity to several possible interferents such as CO, C3 H8 and NO2 . The reproducibility and signal repeatability of the sensor was examined to test the reliability of the sensor. The influence of oxygen variation and humidity in the background on the sensor response was also studied.